Drinkingwater, wastewater and hygiene in Central America and Dominican Republic - Mora-Alvarado, Darner (2024)
This study analysis the latest data on coverage and quality of water for human use and consumption, wastewater sanitation and hygiene or hand washing, in the seven countries that make up the “Forum of Central America and the Dominican Republic in Drinking Water and Sanitation”. This analysis was carried out with the 2022 data from the United Nations Children´s Fund and the World Health Organization “Progress Report on Drinking Water, Sanitation and Hygiene”, prepared by the “Joint Monitoring Program”, published in July 2023. The results placed, Costa Rica as the country with the most progress in “Safely managed water” or drinking quality and in “at least basic” sanitation with 81% and 98%, respectively. Regarding hygiene or hand washing with soap and water, Belice with 90% coverage with “basic service” occupies first place, followed by Costa Rica with 86%, Honduras 85%, El Salvador 81%, Guatemala 77% and Dominican Republic 48%, while Nicaragua and Panama did not provide data. With respect to the Sustainable Development Goals (SDG) for 2030, specifically in the SDG-6, the progress of drinking water and sanitation by 2022 indicates that the proposed goals will not be achieved by the end of 2030, unless investments in the projects are accelerated and increased of drinking water and sanitation.